1998
DOI: 10.1677/joe.0.1560245
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin depletion does not alter lipopolysaccharide-induced activation of the rat paraventricular nucleus

Abstract: We have investigated the effects of serotonin depletion on immune-mediated activation of the hypothalamopituitary-adrenal (HPA) axis. Corticotrophin-releasing factor (CRF) mRNA, c-fos mRNA and Fos peptide responses in the paraventricular nucleus (PVN) together with circulating levels of corticosterone were assessed in response to i.p. injections of three doses of lipopolysaccharide (LPS) both in control animals and animals pretreated with p-chlorophenylalanine (PCPA).Conscious animals received either an i.p. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
5
9
3
Order By: Relevance
“…injection of LPS [1, 9, 11]. Previous results from our group have demonstrated that peripheral administration of this dose, from this particular batch of LPS is insufficient to cause elevations in CRH mRNA within the PVN, thus suggesting that its actions are mediated via central mechanisms in this study [21]. We have further noted a significant increase in both c-fos mRNA and Fos protein in the PVN and the A1 and A2 regions of the brainstem, confirming previous results concerning activation of the HPA axis and c-fos mRNA and Fos peptide following central injection of immune modulators [11, 29, 30].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…injection of LPS [1, 9, 11]. Previous results from our group have demonstrated that peripheral administration of this dose, from this particular batch of LPS is insufficient to cause elevations in CRH mRNA within the PVN, thus suggesting that its actions are mediated via central mechanisms in this study [21]. We have further noted a significant increase in both c-fos mRNA and Fos protein in the PVN and the A1 and A2 regions of the brainstem, confirming previous results concerning activation of the HPA axis and c-fos mRNA and Fos peptide following central injection of immune modulators [11, 29, 30].…”
Section: Discussionmentioning
confidence: 71%
“…In intact animals, following acute stress, there is a peak in c-fos mRNA and plasma CORT concentration after 30 min. This is in contrast to the response to LPS which has a later onset and is more sustained, with peaks in CORT and c-fos expression occuring around 3 h after injection [21, 29, 30, 31]. In a previous study we were unable to determine the presence of c-fos mRNA within the PVN 30 min after LPS, but this increase was apparent after 3 h [21].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The mechanisms whereby normal adrenal response to LPS was found in SKF-64139-treated rats remain to be elucidated; however, depletion of endogenous serotonin, a positive modulator compound of the HPA axis activity [33], in rats resulted in impaired ACTH secretion after LPS [34] accompanied by a normal adrenal response [34,35]. Also, we found that inhibition of the central PNMT activity resulted in enhanced hypothalamic vasopressinergic activity (from parvicellular or magnocellular or both origins) which could contribute, as a compensatory mechanism under sustained EPI inhibition, to a normal glucocorticoid release during acute endotoxemia by stimulating adrenal V1a receptors [36].…”
Section: Discussionmentioning
confidence: 99%